2016
DOI: 10.2306/scienceasia1513-1874.2016.42.332
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and fruit quality of selected papaya breeding lines

Abstract: Nine selected S 3 papaya breeding lines were evaluated for their antioxidant properties and fruit quality. The 14 antioxidant properties and fruit quality traits measured in this study showed significant genotypic differences. KK80 showed the highest ascorbic acid content (114 ± 20 mg/100 ml), antioxidant activity (8.0 ± 1.3 µmol ascorbic acid equivalents/g fresh weight [FW]), and total phenolic compounds (72.2 ± 5.8 mg gallic acid equivalents/100 g FW). KD7 contained the highest amounts of total flavonoid (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…Costa (2012) also found that the exposure of papaya fruits to ozone did not change vitamin C contents. The average vitamin C value in this study was 82 g 100g -1 (Table 3), which is close to values obtained by other studies in literature (REIS et al, 2015a, b;IAMJUD et al, 2016). In studies of pineapple, banana, papaya and grapes exposed to ozone, vitamin C content decreased (ALOTHMAN et al, 2010;YEOH et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…Costa (2012) also found that the exposure of papaya fruits to ozone did not change vitamin C contents. The average vitamin C value in this study was 82 g 100g -1 (Table 3), which is close to values obtained by other studies in literature (REIS et al, 2015a, b;IAMJUD et al, 2016). In studies of pineapple, banana, papaya and grapes exposed to ozone, vitamin C content decreased (ALOTHMAN et al, 2010;YEOH et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…Methods such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) have been used to determine antioxidant activity in many plant extracts 2, 3, 7. Previous studies7, 8, 9, 10, 11 showed that DPPH, ABTS, and FRAP can be used to determine the antioxidant potential of fruits, vegetables, beverages, and food.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation was reported between yield, fruit size, and bioactive compound content [3,54,55]. Therefore, the content of these bioactive substances in tomatoes depends on the harvest, the agronomic interventions, and the genotype analyzed.…”
Section: Principal Components Analysis (Pca)mentioning
confidence: 99%